2018
DOI: 10.1371/journal.pone.0198609
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling regulates the responses of lipopolysaccharide-stimulated macrophages in the presence of immune complexes

Abstract: Macrophages exhibit diverse effector phenotypes depending on the stimuli and their microenvironment. Classically activated macrophages are primed with interferon (IFN)γ and stimulated with pathogen-associated molecular patterns. They produce inflammatory mediators and inflammatory cytokines, such as IL-12. In the presence of immune complexes (ICs), activated macrophages have decreased IL-12 production and increased IL-10 production and presumably act as regulatory macrophages. Notch signaling has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…These data have been confirmed by Xu and collaborators that showed in macrophages isolated from Notch-1 -/mice a decreased basal and LPS-induced NF-κB and HIF-1α activation, indicative that induction of the M1 pathway is dependent on Notch signaling [274]. Defects in NF-κB p50 nuclear localization were observed in DAPT-treated macrophages and in RBP-Jκ-deficent macrophages, indicative of crosstalk between Notch and NF-κB pathways [275]. Lastly, DAPT treatment during MI diminished the number of macrophages in the infarcted area and significantly increased the M2 macrophage polarization [276], data resembling those obtained by Singla et al that confirmed reduction of the proinflammatory M1 phenotype following monocyte treatment with DAPT or Notch-1 siRNA [277].…”
Section: Notch In Macrophagessupporting
confidence: 70%
“…These data have been confirmed by Xu and collaborators that showed in macrophages isolated from Notch-1 -/mice a decreased basal and LPS-induced NF-κB and HIF-1α activation, indicative that induction of the M1 pathway is dependent on Notch signaling [274]. Defects in NF-κB p50 nuclear localization were observed in DAPT-treated macrophages and in RBP-Jκ-deficent macrophages, indicative of crosstalk between Notch and NF-κB pathways [275]. Lastly, DAPT treatment during MI diminished the number of macrophages in the infarcted area and significantly increased the M2 macrophage polarization [276], data resembling those obtained by Singla et al that confirmed reduction of the proinflammatory M1 phenotype following monocyte treatment with DAPT or Notch-1 siRNA [277].…”
Section: Notch In Macrophagessupporting
confidence: 70%
“…Our results revealed that stromal score was strongly and positively correlated with CALD1 (cor = 0.85 and 0.82, P < 0.001) and CCL2 (cor = 0.81 and 0.79, P < 0.001) expressions in the two datasets, indicating that signals from intricate CALD1 , CCL2 , and stromal interactions might drive M2 macrophage activation and polarization. Furthermore, GSEA disclosed that high expression of CALD1 was correlated with several immunoregulation pathways associated with M2 macrophage activation and recruitment, such as cytokine–cytokine receptor interaction, leukocyte transendothelial migration, vascular smooth muscle contraction, TGF-beta signaling pathway, and MAPK signaling pathway ( Jiang et al, 2017 ; Wongchana et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…They modulate the balance between humoral and cell-based immune responses and regulate the maturation, growth, and responsiveness of particular cell populations. Interleukin 1 beta (IL-1β) promotes antimicrobial immunity in macrophages, interferon gamma (IFNγ) and tumor necrosis factor alpha (TNF-α) participate in cell-mediated immune responses, and IL-4 and IL-6 promote humoral or allergic responses [ 26 ]. As shown in Figure 5 , the levels of IL-1β, IL-4, IL-6, IFN-γ, and TNF-α in serum were significantly decreased in the CTX group compared with the normal group ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%